Waste Portable Batteries and Accumulators Management in Compliance with European Union Requirements in Ukraine: Present State and High Priority Activities - SHEVCHENKO, Тetiana; KOBLIANSKA, Inna; MARKOVA, Olena (Journal of Environmental Management and Tourism, 2017)
This study is aimed to determine the high priority activities for forming a separate collection system of waste portable batteries and accumulators in Ukraine to fulfil the European Union (EU) requirements. The necessity to create the State Agency of Ukraine for the recycling of waste electrical and electronic equipment and waste batteries and accumulators as well as the Special Fund for financing the handling processes of this type of waste are substantiated; the main objective of such Agency is to provide the most comprehensive collection and disposal of these types of waste by centralizing administrative functions of systems of handling them.